Agency in meso-level language policy planning in the face of macro-level policy shifts: a case study of multilingual education in a Chinese tertiary institution. Issue 1 (15th March 2021) - Chen, Xiuwen; Tao, Jian; Zhao, Ke
ABSTRACT: In contrast to the waning interest in learning languages other than English (LOTEs) worldwide, mainland China is pursuing to diversify LOTE education because of the 'Belt and Road Initiative.' In response to language policy shifts, individual stakeholders in local contexts such as universities have to take actions to initiate LOTE programs or courses. However, there is still a paucity of research through an in situ lens into meso-level language policy planning (LPP) and implementation. To address this research gap, this study aims to obtain an in-depth understanding of the agentive actions of two groups of individual stakeholders at institutional level: people with power, and people with expertise. Drawing on semi-structured interviews with seven individual actors, the findings reveal that first, although these individual actors demonstrated agency in responding to macro-level language policy changes, the agency that they actually exercised was relatively limited in terms of the diversification of LOTE education. Second, by examining contextual and personal features, we identified multiple factors that mediate individual actors' agency in implementing top-down language policy. These findings may help orient language policy makers to create supportive contexts for the exercise of individual agency at local context in LPP and implementation.